Fabrication of the hexagonal Si nanorod arrays using the template of polystyrene nanospheres in monolayer dispersion. (March 2014) - Yue, Chuang; Li, Jing; Kang, Junyong
Silicon etching is an essential fabrication step in micro-/nanoelectromechanical systems. In this article, the inductive coupled plasma etching technology using monolayer polystyrene nanospheres as the template provides a feasible top-down dry etching method in silicon substrates. The size of the polystyrene nanosphere templates coated on the silicon substrate was adjusted using O2 plasma etching, and the subsequent inductive coupled plasma etching process was applied to produce the silicon nanorods by alternatively employing etching gas SF6 and protective gas C4 F8 . The O2 plasma etching time on the template and the SF6 /C4 F8 flow rate for etching Si substrate were optimized in order to obtain the silicon nanorod structures in the hexagonal morphologies with good verticality, uniformity, and periodicity.